The Role of Research in Shaping Young Entrepreneurial Minds - LARASDIPUTRA, Gde Deny; MARDIKA, Agus Putra (Journal of Tourism Economics and Policy, 2025)
This study aims to provide an understanding that research is not merely an academic formality but can also serve as a valuable asset in the world of entrepreneurship. The concept of Curiosity-Driven Entrepreneurship emphasizes that curiosity plays a crucial role in discovering business opportunities and creating innovations. Through research, students can sharpen their analytical skills, identify market trends, and explore sustainable business potentials. This study highlights success stories of entrepreneurs who started from a place of curiosity, such as the founder of Instagram who studied digital user behavior before creating a platform that has become a global business ecosystem, and Poison Coffee Shop, which successfully developed unique marketing strategies based on the exploration of trends and consumer preferences. By understanding how research can be applied in the business world, students are expected to shift their paradigm about research from a burdensome task to a strategic skill that can support their future success.